Distribución alélica de 15 loci STRs autosómicos en la zona nororiental de Perú - Montalvo Aguirre, Ronald Linderman (2019)
Genetic variability in repetitive DNA is a forensic tool for the study of human populations; include the identification of individuals or kinship relationships between them. This study aimed to characterize the allelic distribution in 15 autosomal STR loci in the northeastern region from Peru: Tumbes, Piura, Lambayeque, La Libertad, Cajamarca and Amazonas. The analysis of the genetic diversity of all the STR loci analyzed (D8S1179, D21S11, D7S820, CSF1PO, D3S1358, TH01, D13S317, D16S539, D22S1338, D19S433, vWA, TPOX, D18S51, D5S818 and FGA ) allowed us to obtain a total of 147 alleles in total, and a cumulative average of 9.8, allele 11 of locus D5S818 being the most common of all analyzed. The FGA locus was the one that exhibited the highest informative data in PD, PE, HO and PIC, obtaining a discrimination power (PD) of 0.9655, exclusion power (PE) of 0.7320, the observed heterozygosity (HO) of 0.8860 and the Polymorphic information content (PIC) was 0.8510, these values being the highest obtained in the present study. All loci showed Hardy-Weinberg equilibrium (p>0.05). The probability of Identity (PI) for two unrelated individuals varied between 0.8170 for the D3S1358 locus and 0.9680 for the FGA locus, with a cumulative value close to 1 (>0.999999999). The values of the FST and RST indicate absent of genetic differentiation (FST= 0.0049; RST= 0.0045; p>0.05) of six populations from northeastern region from Peru. The population structure analysis indicate the absent of population structure in the northeastern region from Peru (K=1). The present study search to contribute with information about to allelic frequency and distribution in STR markers from 6 geographic regions from Peru.